FORMULA ENTERAL “HIKEGA” BERBASIS TEPUNG KACANG HIJAU, TEPUNG KEDELAI DAN TEPUNG MANGGA SEBAGAI ALTERNATIF MAKANAN ENTERAL BAGI PASIEN DIABETES MELLITUS - Sulaeman, Agus; Fitria, Mona; Hapsari , Agustina Indri; Royani, Ani (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
Diabetes mellitus is a non-communicable disease characterized by increased blood sugar levels due to impaired insulin action. In 2013 and 2018, there was an increased prevalence of Diabetes Mellitus in Indonesia from 6.9% to 8.5%. Enteral formulas based on mung bean flour, soybeans and mango flour can be used as an alternative enteral food for diabetes mellitus. The aim of this research is to determine the quality of enteral products based on mung bean flour, soybean flour and mango flour as an alternative for diabetes enteral food regarding organoleptic characteristics, flowability and shelf life. The design of this research was experimental and the sample for the organoleptic test was 25 panelists. The results of the organoleptic test from the two formulas concluded that there was no significant difference, p (0.561) > (0.05). The flow-rate test results for F1 were 17.16 seconds and F2 were 13.13 seconds. Test results for the shelf life of enteral powder formula are ±7 days, there is no change in color, texture and aroma.